Tsaqifa sebagai Metode Menyenangkan dalam Meng-Upgrade Kemampuan Baca Al Quran Orang Dewasa - Ngatipan Ngatipan (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Difficulties in learning to read the Qur’an among adults do not always stem from the quality of teaching materials or instructors, but are often caused by the use of learning methods that are not appropriate to adult learners’ characteristics. Adults possess distinct psychological, physiological, and experiential backgrounds that require learning approaches different from those used for children. Monotonous and rigid instructional methods may hinder motivation and limit learning outcomes, particularly in Qur’anic literacy education. This condition is further compounded by physical limitations commonly experienced by adults and the elderly, such as dental and oral health problems, as well as strong regional language accents that affect pronunciation accuracy. In response to these challenges, the Tsaqifa method was developed as an alternative and practical approach specifically designed for adult beginners who have little or no prior ability to read the Qur’an. This method emphasizes simplicity, flexibility, and learner-centered instruction, enabling participants to gradually improve their Qur’anic reading skills in a supportive and non-intimidating learning environment. Through its application, adult learners are encouraged to regain confidence and motivation in studying the Qur’an, thereby contributing to efforts to reduce Qur’anic illiteracy among adult and elderly communities, particularly in rural areas.